Critical Friends Group for English Language Teachers’ Professional Development - Rayamajhi, Juna (Mangal Research Journal, 2022)
This article entitled 'Critical Friends Group (CFG) for English Language Teachers’ Professional Development' aims to investigate teachers’ perceptions towards CFG for English language teachers’ professional development. This is a qualitative research method based on narrative inquiry. The data was collected from five English language teachers teaching in five different government schools by using semi-structured interview. The participants were selected by using judgmental non- random sampling procedures. The findings showed that teachers perceived CFG as one of the plausible means of their professional development. It helped them to foster collaborative and critical learning in them because they were involved in observation, reading and discussion of various burning issues of English language teaching and learning. It also indicated that teachers perceived CFG as the best platform for enhancing the personal, social and professional development. It has enhanced the professionalism on the part of teachers cultivating the sense of mutual trust and understanding between and among the colleagues.